2012
DOI: 10.1021/es203622v
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Toxic Metals and Persistent Organic Pollutants in Inuit Children Attending Childcare Centers in Nunavik, Canada

Abstract: Arctic populations are exposed to substantial levels of environmental contaminants that can negatively affect children’s health and development. Moreover, emerging contaminants have never been assessed in Inuit children. In this study, we document the biological exposure to toxic metals and legacy and emerging persistent organic pollutants (POPs) of 155 Inuit children (mean age 25.2 months) attending childcare centers in Nunavik. Blood samples were analyzed to determine concentrations of mercury, lead, polychl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…BDE-153 is known to be more resistant to metabolism than other congeners (Lupton et al 2009). Compared to a population of Inuit men from Canada, select congeners appeared elevated among St. Lawrence Island residents (O’Brien et al 2012). Geometric mean concentrations of BDE-153 and BDE-47 on St. Lawrence Island were higher, at 8.65 and 10.19 ng/g lw, respectively, than corresponding data from the Canadian Inuit population, at 2.05 and 2.16 ng/g lw, respectively (Dallaire et al 2009).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…BDE-153 is known to be more resistant to metabolism than other congeners (Lupton et al 2009). Compared to a population of Inuit men from Canada, select congeners appeared elevated among St. Lawrence Island residents (O’Brien et al 2012). Geometric mean concentrations of BDE-153 and BDE-47 on St. Lawrence Island were higher, at 8.65 and 10.19 ng/g lw, respectively, than corresponding data from the Canadian Inuit population, at 2.05 and 2.16 ng/g lw, respectively (Dallaire et al 2009).…”
Section: Discussionmentioning
confidence: 87%
“…This may be due in part to the increased use of deca-BDE in the intervening years. Research in the Canadian Arctic indicated that PBDE levels are higher in young Inuit children than in Inuit adults (O’Brien et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Some early studies in the 1990s have confirmed that neonatal exposure to neurotoxic materials (e.g., metals, pesticides, polychlorinated biphenyls) can cause the reduction of habitual behavior abilities (Eriksson et al, 1990, 1991; Fredriksson et al, 1992). Childhood exposure to environmental contaminants can negatively affect children's health and development (Turgeon O'Brien et al, 2012). PBDEs, brominated flame retardants, are widely used in family consumer products and have become a great global concern as environmental organic pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Although some heavy metals such as Fe, Cu, Zn, and Ni were essential for animal and plant metabolism, they were also potential for affecting the neurological system, kidney function, the ossification process, and various other high-level organs [19]. Other metals such as Cd, Cr, and Pb were highly related with bladder cancer, neurotoxicity, and dysfunction of the hematopoietic system [20][21]. It had also been observed that chro-nic exposure to low doses of cancer-causing heavy metals might cause many types of cancer [22].…”
mentioning
confidence: 99%